2018
DOI: 10.1111/mpp.12750
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CRISPR‐Cas systems in the Ralstonia solanacearum species complex

Abstract: Summary Clustered regularly interspaced short palindromic repeats (CRISPRs) are composed of an array of short DNA repeat sequences separated by unique spacer sequences that are flanked by associated (Cas) genes. CRISPR‐Cas systems are found in the genomes of several microbes and can act as an adaptive immune mechanism against invading foreign nucleic acids, such as phage genomes. Here, we studied the CRISPR‐Cas systems in plant‐pathogenic bacteria of the Ralstonia solanacearum species complex (RSSC). A CRISPR‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 123 publications
(117 reference statements)
1
17
0
Order By: Relevance
“…O. S. Gonçalves et al (28) reported that in the presence of CRISPR arrays, 27.9% of CRISPR spacers from Ralstonia genomes targeted prophage elements. In our study, two Ralstonia MAGs from a low temperature environment were devoid of CRISPR systems, implying that representatives of this genus have alternative strategies for defense against mobile genetic elements (43). However, analyses on more Ralstonia genomes are necessary to corroborate this statement.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…O. S. Gonçalves et al (28) reported that in the presence of CRISPR arrays, 27.9% of CRISPR spacers from Ralstonia genomes targeted prophage elements. In our study, two Ralstonia MAGs from a low temperature environment were devoid of CRISPR systems, implying that representatives of this genus have alternative strategies for defense against mobile genetic elements (43). However, analyses on more Ralstonia genomes are necessary to corroborate this statement.…”
Section: Discussionmentioning
confidence: 74%
“…Upon exposure to a virulent phage under laboratory conditions, the CRISPR array of Ralstonia solanacearum strain CFBP2957 did not acquire new spacers from viral protospacers. This demonstrates the CRISPR system's inefficiency in viral eradication and suggests alternative antiviral mechanisms in this Ralstonia strain (43). More recently, a publication reported that in the presence of CRISPR arrays, 27.9% of spacers from Ralstonia genomes targeted prophage elements (28).…”
Section: Discussionmentioning
confidence: 97%
“…This system utilizes numerous Cas proteins for the recognition and cleavage of targeted nucleic acids, therefore the genome of the RSSC strains contains the following Cas proteins: Cas1_0_IE, Cas2_0_IE, Cas3_0_IE, Cas5_0_IE, Cas6_0_IE, Cas7_0_IE, Cse1_0_IE, and Cse2_0_IE. Besides the mentioned strains, other strains from phylotypes I and IV not included in Table 2 show the presence of CRISPR-Cas system as da Silva, Xavier et al (2019) reported. This result indicates that the CRISPR-Cas system is present in all phylotypes although it is not widely distributed across strains.…”
Section: Clustered Regularly Interspaced Short Palindromic Repeats (Cmentioning
confidence: 89%
“…The CRISPR-Cas system in RSSC was first described by da Silva, Xavier et al (2019). They found this system in 31% of RSSC genomes present in public databases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation